Economic evaluation of "healthy beginnings" an early childhood intervention to prevent obesity. (27th March 2014) - Hayes, Alison; Lung, Tom; Wen, Li Ming; Baur, Louise; Rissel, Chris; Howard, Kirsten
<x xml:space="preserve">Abstract</x> Objective To determine the costs and cost‐effectiveness of an early childhood home visiting program delivered to families in socio‐economically disadvantaged areas of Sydney, Australia during 2007‐2010. Methods Economic evaluation of a randomized controlled trial, the healthy beginnings (HB) trial, from the perspective of the health funder. Intervention resources were determined from local health district records in 2012 $AUD. Health‐care resource utilization was determined through patient‐level data linkage. Results The cost of HB intervention in the clinical trial over 2 years was $1309 per child (2012 $AUD). The incremental cost‐effectiveness ratio was $4230 per unit BMI avoided and $631 per 0.1 reduction in BMI z‐score. It was estimated that the program could be delivered in practice for $709 per child; with incremental cost‐effectiveness ratios of $2697 per unit BMI avoided and $376 per 0.1 reduction in BMI z‐score. Conclusions We present the first economic evaluation of an effective obesity prevention initiative in early childhood. HB is a moderately priced intervention with demonstrated effectiveness that offers similar or better value for money than existing obesity prevention or treatment interventions targeted at older children.